Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1001/jamanetworkopen.2022.10871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of T-cell Reactivity to the SARS-CoV-2 Omicron Variant by Immunized Individuals

Abstract: IMPORTANCEThe emergence of the highly contagious Omicron variant of SARS-CoV-2 and the findings of a significantly reduced neutralizing potency of sera from individuals with previous SARS-CoV-2 infection or vaccination highlights the importance of studying cellular immunity to estimate the degree of immune protection to the new SARS-CoV-2 variant. OBJECTIVE To determine T-cell reactivity to the Omicron variant in individuals with established (natural and/or vaccine-induced) immunity to SARS-CoV-2. DESIGN, SETT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 16 publications
6
39
2
Order By: Relevance
“…In our study, T-cell responses to spike peptide pools from Wuhan and Omicron variants showed largely comparable results. This is in line with recent data reporting that the cellular response to SARS-CoV-2 variants is preserved in most infected and vaccinated individuals 43 47 . As T-cell responses to SARS-CoV-2 spike peptides could be influenced by pre-existing cross-reactive immunity against other human corona viruses 48 , 49 , we analyzed responses to the more variable S1 part containing the RBD and more conserved membrane-proximal S2 moiety of the spike protein separately.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, T-cell responses to spike peptide pools from Wuhan and Omicron variants showed largely comparable results. This is in line with recent data reporting that the cellular response to SARS-CoV-2 variants is preserved in most infected and vaccinated individuals 43 47 . As T-cell responses to SARS-CoV-2 spike peptides could be influenced by pre-existing cross-reactive immunity against other human corona viruses 48 , 49 , we analyzed responses to the more variable S1 part containing the RBD and more conserved membrane-proximal S2 moiety of the spike protein separately.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, despite exponential differences in neutralising antibody titres, SARS-CoV-2 vaccines of different platforms including mRNA, adenoviral vector and inactivated vaccines have been shown to produce potent T cell responses and very high effectiveness against hospitalisation 31,[47][48][49] . Multiple lines of evidence support the contention that T cells play a major role in mediating protection against severe COVID-19 31,[49][50][51][52][53][54][55][56] . Therefore, our T cell results suggest adolescents receiving either vaccine are also protected from severe COVID-19.…”
Section: Discussionmentioning
confidence: 88%
“…against the Omicron S protein are largely preserved (>80%) in most vaccinated and previously infected adults 49,[51][52][53][54][55] . This lasting cellular immunity is one of many possibilities that contributes to the high clinical effectiveness of 2 doses of BNT162b2 doses against hospitalisation and death during the initial Omicron wave [64][65][66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Released IFN-γ was significantly reduced when cells were incubated with the peptide compared with those of the ancestral strain. However, the overall reactivity to the peptide library of the full-length protein was largely maintained [36]. SARS-CoV-2-specific T cells were detected up to 6 months after all vaccination, and no significant differences were detected between WT-and variant-specific CD4+ or CD8+ T cell responses, including omicron [37].…”
Section: Discussionmentioning
confidence: 95%